2013
DOI: 10.2478/s13380-013-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of tea polyphenols on the blood-brain barrier

Abstract: This study was to investigate the protective effects of tea polyphenols on the blood-brain barrier (BBB) of rats with global cerebral ischemia/reperfusion (GCIR) injury. Sprague Dawley rats underwent four-vessel occlusion to construct the model of GCIR. Half an hour before complete occlusion, they were treated with tea polyphenols (TP) (6.4%; 100 or 200 mg/kg) via tail intravenous injection. 24 h after reperfusion, BBB permeability was evaluated by measuring brain water content (BWC) and residual amount of Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2), possibly due to the actions of the rich polyphenol contents in FRHT as previously reported for other teas (Lee et al 2004, ArunaDevi et al 2010. Tea polyphenols (Xue et al 2013), Lycium barbarum extracts (Yang et al 2012), dietary olive leaf extract (Mohagheghi et al 2011) and lavender extract (Rabiei and Rafieian-Kopaei 2014) have all been shown to potentially protect the BBB against ischemic damage albeit via poorly understood mechanisms of action. We suggest that the observed BBB disruption and brain oedema protection effects of FRHT could have occurred either due to attenuation of oxidative stress damage to capillary endothelial cells and basement membrane (Panickar et al 2013, Krueger et al 2015, reversal of the ischemia-induced reduction in the expression of the tight junction proteins claudin-5, occludin and ZO-1 as seen with green tea polyphenols (Liu et al 2013) or modulation of paracellular permeability to prevent disruption of the tight junctions between brain microvascular endothelial cells (Yang et al 2016).…”
Section: Discussionmentioning
confidence: 88%
“…2), possibly due to the actions of the rich polyphenol contents in FRHT as previously reported for other teas (Lee et al 2004, ArunaDevi et al 2010. Tea polyphenols (Xue et al 2013), Lycium barbarum extracts (Yang et al 2012), dietary olive leaf extract (Mohagheghi et al 2011) and lavender extract (Rabiei and Rafieian-Kopaei 2014) have all been shown to potentially protect the BBB against ischemic damage albeit via poorly understood mechanisms of action. We suggest that the observed BBB disruption and brain oedema protection effects of FRHT could have occurred either due to attenuation of oxidative stress damage to capillary endothelial cells and basement membrane (Panickar et al 2013, Krueger et al 2015, reversal of the ischemia-induced reduction in the expression of the tight junction proteins claudin-5, occludin and ZO-1 as seen with green tea polyphenols (Liu et al 2013) or modulation of paracellular permeability to prevent disruption of the tight junctions between brain microvascular endothelial cells (Yang et al 2016).…”
Section: Discussionmentioning
confidence: 88%
“…In the context of studying early brain damage in other SAH models (26,27), the highlight lies in the inclusion of a sham-operated group as a control, allowing for a comparison with the SAH group and the use of TPPs for treating early brain injury. Nevertheless, research on the role of TPPs in modulating the PI3K/Akt pathway in the context of post-SAH brain injury is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, reports focused on the effect of tea on DM-induced alterations in brain’s metabolism are very scarce. Previous studies have shown that tea polyphenols inhibit inflammatory response and have neuroprotective effects after ischemia reperfusion injury [ 87 ], and may be able to protect the BBB integrity [ 117 ]. Moreover, caffeine is one of the main tea phytochemicals and has the ability to cross BBB exerting pivotal effects on the brain and acting in the CNS.…”
Section: Tea Chemical Compositionmentioning
confidence: 99%